The effect of intermediate layer densification on the critical current of a Bi-2223 superconducting joint. (1st March 2023) - Takeda, Y; Nishijima, G; Inoue, K; Takano, Y; Kitaguchi, H
Abstract: The effect of intermediate layer densification on the critical current ( I c ) of Bi-2223 superconducting joints was quantitatively studied. First, we evaluated the phase purity, density, and intergrain critical current density ( J c ) of Bi-2223 thick film samples simulating the intermediate layer. The samples were uniaxially pressed to increase the film density. After two heat treatments of the pressed film, an increase in J c was achieved. Second, we fabricated superconducting joints by synthesizing an intermediate layer between two Bi-2223 tapes. Applying a uniform uniaxial pressure on the joint resulted in the formation of a homogeneous structure. This process enables the reproducible fabrication of superconducting joints with high n values. The I c of the superconducting joint was increased by intermediate pressing (IP) and two heat treatments. However, pressing at high pressures can mechanically damage filaments in the Bi-2223 tapes, leading to a decrease in I c . Sample characterization showed that the optimum IP pressure range to produce high I c was 1.5–2 × 10 8 Pa. We confirmed that pressing densified the intermediate layer of the superconducting joints. Our experimental results and analyses reveal that densification of the intermediate layer increases the I c of Bi-2223 superconducting joints.